UJI DAYA HAMBAT EKSTRAK UMBI RUMPUT TEKI (Cyperus rotundus L.) TERHADAP BAKTERI Escherichia coli - Rafia; Athia K. Kasim (Jurnal Ilmiah Kesmas -IJ, 2022)
A research has been carried out with the title "Test of Inhibition of Teki Grass Bulbs (Cyperus rotundus L.) against Escherichia coli bacteria". This study aims to determine the inhibition power of nut grass root extract against Escherichia coli bacteria and to determine what concentration is the highest or exceeds the positive control in inhibiting the growth of Escherichia coli. The method used is the disc diffusion method, the research was conducted in the laboratory of the Pharmacy Bina Pharmacy Academy. Based on the identification results, the active compounds of nut grass tubers contain alkaloid compounds, flavonoids, saponins and tannins. From the research results, nut grass tuber infusion with a concentration of 5%, 10%, 15%, 20%, and 25% all showed antibacterial activity. And the results at a concentration of 25% are close to positive control. So it can be concluded that the nut grass tubers have antibacterial activity.